Liaison Interpreting in Radio Settings: An interaction with two levels of communication - Pedro Jesús, Castillo Ortiz (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Media interpreting is probably the setting where the interpreter is most exposed to a large, yet mostly unknown and unseen audience. It could be argued, in fact, that it is through media interpreting that the general public creates its own notion of what an interpreter is (their role, skills, etc.). Although a growing field (see Castillo Ortiz, 2015b), research on interpreting in the highly specific and demanding contexts of different media is still rather scarce and this applies in particular to liaison interpreting on the radio, where it is almost non-existent. Previous studies on liaison interpreting (Wadensjö, 1992, 1998; Hatim and Mason, 1997; Mason, 2000, 2001, 2006; Viaggio, 2004; Cicourel, 1992, among others) and social interaction in general (Goffman, 1971, 1981) show how the context determines most of the interactions, relationships and utterances of the interlocutors (both primary interlocutors and the interpreter) during an interpreter mediated event. Against this theoretical background, I have analysed the radio setting, with special attention to interviews and the role of the broadcaster. For my data analysis I have compiled a small sample of data consisting of two of interpreter-mediated radio interviews from Radio 3, a station which is part of the Spanish State Broadcasting Company and which frequently uses liaison interpreting to enable multilingual communication in its programmes. The results obtained so far indicate that this setting seems to require particular skills from the interpreter that have not been covered by current literature.Finally, this article also aims at opening new avenues of research not only in the field of Liaison Interpreting and Radio Studies, but also regarding the analysis of the interpreting market in this context and interpreter training.
Keywords: media interpreting; liaison interpreting; radio; context